PEDAGOGICAL CONDITIONS FOR DEVELOPING THINKING ACTIVITY IN PRIMARY SCHOOL PUPILS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article explores the pedagogical conditions necessary for enhancing thinking activity in primary school pupils. It examines the essence of thinking activity in the learning process, as well as the methods and environmental factors that stimulate cognitive engagement in children. The author emphasizes the importance of an active, creative, and student-centered teaching approach to promote independent and critical thinking from an early age. Effective strategies, such as interactive methods, technological integration, and a psychologically supportive learning environment, are considered essential for fostering high-level thinking skills in young learners.